1997
DOI: 10.1111/j.1600-0897.1997.tb00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Leukocytes Selectively Increase Secretion of IL‐4 in Peripheral Blood During Normal Pregnancies: Demonstrated by a Novel One‐Way MLC Measuring Cytokine Secretion

Abstract: The findings indicate a selective immune deviation toward Th2, which may protect the fetus from rejection and thus may be an important homeostatic mechanism in normal pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
3
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 19 publications
7
60
3
2
Order By: Relevance
“…Furthermore, stimulation with paternal leukocytes increases the secretion of IL-4 by maternal PBMC during normal pregnancy (Ekerfelt et al 1997). Previous studies have reported a high secretion of Th2-like cytokines at the time of delivery of normal pregnancies and increased Th1-like cytokines at the time of a spontaneous abortion (Marzi et al 1996;Makhseed et al 2001).…”
Section: Pregnant Women Havementioning
confidence: 98%
“…Furthermore, stimulation with paternal leukocytes increases the secretion of IL-4 by maternal PBMC during normal pregnancy (Ekerfelt et al 1997). Previous studies have reported a high secretion of Th2-like cytokines at the time of delivery of normal pregnancies and increased Th1-like cytokines at the time of a spontaneous abortion (Marzi et al 1996;Makhseed et al 2001).…”
Section: Pregnant Women Havementioning
confidence: 98%
“…We have previously shown that pregnant women have a higher number of both IFN-γ and IL-4 expressing mononuclear cells in blood than non-pregnant women (Matthiesen et al, 1998;Matthiesen et al, 2003). Furthermore, pregnant women showed increased numbers of IL-4 secreting cells in blood in response to paternal allo-antigens, indicating a Th2-response directed against the fetus during pregnancy (Ekerfelt et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The alloreactivity and cytokine secretion from responder cells, i. e. maternal lymphocytes, was determined by using a one-way MLC as previously described (Ekerfelt et al, 1997). PHA and wells containing TCM only.…”
Section: Mixed Leukocyte Culture (Mlc)mentioning
confidence: 99%
“…Further, it remains obscure if the previous observations reflect an increase of actual suppressive Tregs since more specific markers such as Foxp3 have not been thoroughly investigated previously. As pregnancy could be considered a state of controlled immune activation (25,26), possibly due to exposure and awareness of fetal antigens, the CD4 + CD25 high expansion seen during pregnancy might reflect an increase of activated CD4 + T cells. Thus, in such settings, Tregs should be better characterised by proteins such as Foxp3, CTLA-4, HLA-DR and the recently described marker CD127 low .…”
Section: And T H 2 Like Reactions As Demonstrated By An In Vitromentioning
confidence: 99%
“…Thirty-eight healthy pregnant women with no signs of pregnancy complications at inclusion (pregnancy week [24][25][26][27][28] visiting the maternity outpatient care unit in Linköping (Kvinnohälsan), were asked to participate in the study. Obstetrical history of these women is given in table I. Twenty-five women were pregnant for the first time and thirteen had experienced at least one previous pregnancy.…”
Section: Subjectsmentioning
confidence: 99%